Sex differences in sudden cardiac death in a nationwide study of 54 028 deaths. Issue 13 (11th March 2022) - Skjelbred, Tobias; Rajan, Deepthi; Svane, Jesper; Lynge, Thomas Hadberg; Tfelt-Hansen, Jacob
Abstract : Objective: Sudden cardiac death (SCD) is a leading cause of death and is more common among males than females. Epidemiological studies of sex differences in SCD cases of all ages are sparse. The aim of this study was to examine differences in incidence rates, clinical characteristics, comorbidities and autopsy findings between male and female SCD cases. Methods: All deaths in Denmark in 2010 (54 028) were reviewed. Autopsy reports, death certificates, discharge summaries and nationwide health registries were reviewed to identify cases of SCD. Based on the available information, all deaths were subcategorised into definite, probable and possible SCD. Results: A total of 6867 SCD cases were identified, of which 3859 (56%) were males and 3008 (44%) were females. Incidence rates increased with age and were higher for male population across all age groups in the adult population. Average age at time of SCD was 71 years among males compared with 79 among females (p<0.01). The greatest difference in SCD incidence between males and females was found among the 35–50 years group with an incidence rate ratio of 3.7 (95% CI: 2.8 to 4.8). Compared with female SCD victims, male SCD victims more often had cardiovascular diseases and diabetes mellitus (p<0.01). Conclusion: This is the first nationwide study of sex differences in SCD across all ages. Differences in incidence rates between males and females were greatest among young adults and the middle-aged. Incidence rates of SCD among older female population approached that of the male population, despite having significantly more cardiovascular disease and diabetes in male SCD cases.